Pengaruh Kelompok Referensi, Media Sosial Dan Work Of Mouth Terhadap Keputusan Pembelian - Melia Anggraini; Fitriani Fitriani; Vicky F Sanjaya (Jurnal Ekonomi, Manajemen dan Akuntansi (JEMA) Universitas Ngudi Waluyo, 2021)
ABSTRACT This study aims to test the Reference, Social Media and Work Of Mouth groups on purchasing decisions in the millennial generation. The method used in this research is a questionnaire. The sample of this researchis 100 respondents. The static test was performed using the PLS-based Sturcturel Equation Modeling. The validation test uses the loading factor value. while the reliability test used Cronbach's alpha value, composite reliability and Average Variance Extracted (AVE). Of the three hypotheses put forward for the first and second hypotheses are accepted while the third hypothesis is rejected. The conclusion of this study is that the reference group and social media are accepted, while the Work of mount is rejected